2018
DOI: 10.21078/jssi-2018-237-12
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Transportation and Housing Subsidies on Urban Sprawl

Abstract: This paper analyses theoretically the effect of transportation and housing subsidies on urban sprawl, modal choice decisions and urban spatial structure using a spatial general equilibrium model in a monocentric city with two transport modes. Our analysis shows that public transit subsidy leads to urban shrink, whilst subsidizing automobile and housing make the city sprawl. We also find the effects of the other factors on urban sprawl, such as households income and demand, rural land rent, the income tax rate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, its urbanizationsteering potential depends on the complex relation between car and public transport use. Overall, transport taxes might lead to sprawl while public transport subsidies might encourage compactness [8], [10].…”
Section: Instrument Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…However, its urbanizationsteering potential depends on the complex relation between car and public transport use. Overall, transport taxes might lead to sprawl while public transport subsidies might encourage compactness [8], [10].…”
Section: Instrument Analysismentioning
confidence: 99%
“…Moreover, Mendonça et al [8] demonstrated that economic instruments, such as land and property taxes as well as public transport subsidies, have the potential to curb urban sprawl, gentrification and work alongside amenities. Land, property and transport taxes and subsidies have also been considered effective anti-sprawl policies by other authors [10], [14]. Several other authors demonstrate the crucial role that information instruments have in NBS implementation and sustainability promotion [34], [39], [40].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation